Prevalence and Treatment Needs for Early Childhood Caries Among 3–5-Year-Old Children From a Rural Community in Uganda - Musinguzi, Norman; Kemoli, Arthur; Okullo, Isaac (Frontiers in Public Health, 2019)
Introduction Early Childhood caries (ECC) is the term used to describe dental caries in children aged 71 months and below. ECC causes a lot of pain and discomfort in the affected children and is expensive to treat. There is limited data on the prevalence of ECC in preschool children resident in the rural Uganda. Aim: To determine the prevalence and treatment needs for ECC among 3-5-year-old nursery school children in a rural community in Rukungiri District, Uganda. Study design: This was a descriptive cross-sectional study involving 432 nursery school children aged 3-5 years from rural Nyakagyeme sub-county in Ugandan, whose parent/guardians provided Informed consent for their participation. The examination of the participants was done under field conditions and the findings were recorded on individualised modified WHO Oral Health Assessment Forms for children. Data Analysis: The data gathered were analysed using Windows SPSS Version 23.0 computer programme, and descriptive results for the variables obtained and Mann Whitney and Kruskal-Wallis tests used to compare and relate the variables. The P<0.05 was considered statistically significant with the Confidence interval set at 95%. The findings were presented in Tables and Figures. Results A total of 230 (53.2%) male and 202 (46.6%) female participants, with 118 (27.3%), 145 (33.6%), 169 (39.1%) aged 3, 4, and 5 years old respectively, participated in the study. The prevalence of ECC among the participants was 48.6%, with 11.6%, 18.5% and 18.5% recorded for the 3-, 4-, and 5-year old children respectively. The male participants had a higher prevalence (26.1%) than the female counterparts (22.5%). The mean ‘dmft’ for the participants was 2.04 (SD=3.01) with the decay component (dt) contributing to 88.6% of the dental caries experience. The mean ‘dmft’ was 1.79, 2.37 and 1.91 for the 3-, 4- and 5-year old children respectively Conclusion: The prevalence of ECC of 48.6% was moderate in this study population. The high level of unmet treatment need as exemplified by the high dental caries experience, was a cause for concern as this forms a risk factor for caries in the permanent dentition. Key words: Early Childhood caries, Treatment needs, Nursery school children